Mesure des performances dans le secteur routier: État des lieux transnational - Matthew Karlaftis; Konstantinos Kepaptsoglou (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
– Road networks are important lifelines for modern societies. Social prosperity and economic development are directly related to mobility and accessibility of communities and are, therefore, highly dependent upon the existence of high quality road networks. Currently, roadways are the dominant mode of transport, particularly in developed countries. In Europe for instance, over 75% of ground freight transportation is by road, while road passenger transport exceeds 80% (Eurostat, 2012). According to Urban Audit (Urban Audit, 2012), private vehicle usage for work related journeys in major European cities exceeds 40% in most cases, while the same figure for US cities is over 70%. Further, despite worldwide efforts for promoting sustainability and environmentally 'friendly' modes, road users tend to increase on a global scale, as developing countries gradually enter the world of motorization (Pucher et al., 2007).
Keywords: 330